The Royal Commission and Rudnyckyj's Mission: The Forging of Official Multiculturalism in Canada, 1963–71. - Prymak, Thomas M. (University of Toronto Quarterly)
This article discusses the forging of the concept and policy of official multiculturalism in Canada during the 1960s and early 1970s, which largely came out of the work of the Royal Commission on Bilingualism and Biculturalism. In particular, it features the important role played by the linguist Jaroslav Rudnyckyj and by Ukrainian Canadians. The article argues that the term "multiculturalism" was coined and pioneered in Canada prior to its general use elsewhere and that a particular conjunction of demographic realities, and national and even international politics, made this possible.